The infection with HBV and HCV and their relationship to ABO blood group among blood donors - Aljooani, Omar A. A.; Al-Hayani, Noor N.; Mohammed, Mahmood J. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Hepatitis B virus (HBV) and C virus (HCV) known to be transmitted through blood and blood products and has been implicated as a major cause of chronic liver disease and hepatocellular carcinoma worldwide.Objective: This study aim to detect the relationship between the HBV and HCV infections with ABO blood groups and age of blood donor in Al- Ramadi city.Patients & Methods: We conducted Hepatitis B surface antigen test strip (ACON Laboratories) (USA) and HCVAb, as step to detect the infections among blood donors at the laboratories for central blood bank in Alanbar health directory, M.O.H. The results of this study were analyzed statistically using the T-test to find the significance of probability level according to SPSS ver12 program. (P) Value < 0.05 were considered significant.Results: Among (430) volunteer blood donors, there were 71(16.511%) positive for HBs Ag and 12(2.790%) for HCVAb. Hepatitis B and C infections were significantly associated with blood group of the donors; percentage of HBs Ag and HCVAb were found to be higher in donors who has blood group O and lowest in blood group AB donors, while the distribution of Rh in hepatitis infected donors was higher among Rh positive donors. HCV infections show a high percentage at age group (26–35) years old, while the percentage of HBV infections increase with progress of age group among blood donors.Conclusion: There were a significant association between blood group of donors and hepatitis infections and the infections of HCV increase among (26-35) years old blood donors while the HBV infections increase with progress of age groups.